THE LINGUISTIC ETIQUETTE OF GREETING AND LEAVE-TAKING IN JORDANIAN ARABIC - Rababa`hMahmoud Ali; Malkawi, Nibal Abd Alkareem (European Scientific Journal, ESJ, 2012)
This paper investigates the sociolinguistic politeness of greeting followed by Jordanian people in day-to-day social interactions. Politeness is one of the most important aspects of human communication in which human beings have to observe the basic conventions of politeness if they want to exist in peace together. Jordanians genuinely tend to oil the wheels of social interaction by adhering to a set of long-standing conventions. They do this not merely to make life easy for themselves, but out of respect, consideration and affection for their fellows. This study examines the different types of Arabic greeting sequences and the sociolinguistic factors that account for their structuring. Jordanians adhere to strict conventions of polite behavior which are derived from the Islamic teachings and Arabic traditions to keep channels open and keep peaceful relations with others. Greetings in Arabic are very essential for the establishment of interpersonal relationships and for the introduction of a business or a social topic. The study suggests that deference to age, sex, context of situation and time are important factors in the structuring of greetings in Jordanian Arabic. There are some socio-cultural and socio-religious rules of initiating greetings in general. The most common and most polite greeting term is "assalaamu 9alaykum" (Peace be upon you) due to its socio-religious significance. The Apostle of Allah ordered Muslims to spread this greeting among themselves. The Prophetic Traditions also explain that this greeting was the greeting of Adam and of his offspring. Therefore, this term is considered the most polite greeting. There are other time-specific greetings and context or situation-specific terms which denote the social competency of their users.